Books on Asia from the Near East to the Far East. - Birnbaum, Eleazar.
1 online resource (358 pages)
Keywords: This is a selected, annotated list of some 2,000 books on Asia in English and French currently in print, chosen with the aim of providing a long-term historical perspective for the general reader..